HUBUNGAN INFEKSI SOIL TRANSMITTED HELMINTHS DENGAN KADAR Hb PADA ANAK SEKOLAH DASAR DI DESA NELAYAN KOTA BENGKULU - Marlina, Leni (JURNAL MEDIA KESEHATAN, 2012)
helminthiasis is a disease caused by a worm or helminth. Worm disease is a neglected infectious diseases / Neglected Infectious Disease (NIDS), which can lead to declining health, nutrition, intelligence and productivity. Factors that could cause the high incidence of worm disease is sanitation, hygiene, education level, socio-economic, knowledge, attitudes, behavior and geographical conditions. This study aimed to determine the relationship Soil transmitted helminth infections with Hb levels in elementary school children in the fishing village town of Bengkulu. This study was a cross sectional analytic. Subjects were four primary school pupils in Desa Nelayan of Bengkulu. Large sample of 185 samples. Sampling with simple random sampling technique. Examination of faeces by direct methods. Analysis of the samples by using the t test. The result showed no significant association with Hb STH infection (p = 0.09), no significant relationship with personal hygiene STH infection (p = 0.89), no significant association with the school environment sanitation STH infections (p = 0.34) and no significant relationship with the environmental sanitation STH infection (p = 0.70) in the elementary school children in Desa Nelayan of Bengkulu. The school have to provide counseling so that maintain the health of the prevention efforts that can reduce STH infections in elementary school children.